2022
DOI: 10.3390/jcm11164885
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Effective Circulating Volume with Sublingual Red Blood Cell Velocity and Microvessel Pressure Difference: A Clinical Investigation and Computational Fluid Dynamics Modeling

Abstract: The characteristics of physiologic hemodynamic coherence are not well-investigated. We examined the physiological relationship between circulating blood volume, sublingual microcirculatory perfusion, and tissue oxygenation in anesthetized individuals with steady-state physiology. We assessed the correlation of mean circulatory filling pressure analogue (Pmca) with sublingual microcirculatory perfusion and red blood cell (RBC) velocity using SDF+ imaging and a modified optical flow-based algorithm. We also reco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…Previous studies of sublingual microcirculation during noncardiac surgery also reported considerable heterogeneity in microcirculatory flow among individuals, as well as substantial interindividual variability. 8,26,27 In general, available evidence suggests that microcirculatory perfusion is preserved during general anesthesia and elective non-cardiac surgery when MAP is maintained within a normal range or slightly higher. 28 In contrast, there may be an association between microcirculatory tissue perfusion and outcome in high-risk non-cardiac surgery patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies of sublingual microcirculation during noncardiac surgery also reported considerable heterogeneity in microcirculatory flow among individuals, as well as substantial interindividual variability. 8,26,27 In general, available evidence suggests that microcirculatory perfusion is preserved during general anesthesia and elective non-cardiac surgery when MAP is maintained within a normal range or slightly higher. 28 In contrast, there may be an association between microcirculatory tissue perfusion and outcome in high-risk non-cardiac surgery patients.…”
Section: Discussionmentioning
confidence: 99%
“…Within this range, microcirculation can be highly adaptive to its cellular environment and can be autoregulated independent of changes in systemic blood pressure. 8,26 However, monitoring of sublingual microcirculation can yield important physiologic information in patients with hypotension, comorbidities, or those with high levels of chronic systemic inflammation. 27 The latter can decrease capillary perfusion and vascular integrity and impair the ability of the microvasculature to coordinate a vasodilatory response.…”
Section: Per S Pec Tive Smentioning
confidence: 99%
See 1 more Smart Citation
“…Although extreme hyperoxia is associated with poor neurologic outcomes [ 70 , 71 , 72 , 73 ], “critical” hypoxia does not equate to a specific oxygen concentration. Of note, many tissues function physiologically at levels equivalent to an atmosphere of 5% oxygen, and some at levels as low as 1% oxygen [ 74 , 75 ], and therefore, optimizing perfusion may be more important than setting a specific oxygenation target in anesthetized patients [ 76 , 77 , 78 ].…”
Section: Respiratory Managementmentioning
confidence: 99%
“…Inflammation and increased reactive oxygen species formation may affect all organ systems, including the lungs. Thus, the attenuation of NO exhalation by propofol and sevoflurane reported by Vekrakou et al may imply the preservation of bronchial microcirculatory perfusion and decreased NO synthesis, due to the immunomodulatory effects and the effects on microcirculation mediated by anesthetics in steady states [ 30 , 31 ] and in disease [ 32 , 33 ]. All the aforementioned factors can improve heart–lung interactions and facilitate the application of lung-protective ventilation strategies, preventing injurious mechanical stretching of lung parenchyma, and subsequent progression to fibrosis in patients with ARDS [ 34 ].…”
mentioning
confidence: 99%